The tortoise versus the hare - Possible advantages of microparticulate zerovalent iron (mZVI) over nanoparticulate zerovalent iron (nZVI) in aerobic degradation of contaminants. (15th November 2016) - Ma, Jinxing; He, Di; Collins, Richard N.; He, Chuanshu; Waite, T. David
Abstract: A comparative study of the ability of microparticulate zerovalent iron (mZVI) and nanoparticulate zerovalent iron (nZVI) to oxidize a target compound (in this study, 14 C-labelled formate) under aerobic conditions has been conducted with specific consideration given to differences in reaction mechanisms. Results of Fe K -edge extended X-ray absorption fine structure (EXAFS) spectroscopy showed that mZVI underwent a slow transformation to ferrihydrite while nZVI, in contrast, rapidly transformed into lepidocrocite. The behavior of mZVI (compared to nZVI) could be attributed to either (i) a lower reactivity with oxygen and/or water, (ii) surface passivation by ferrihydrite resulting in reduced electron conductivity, and/or (iii) the relatively low concentration of Fe(II) which, in the case of nZVI, catalyzed the transformation of ferrihydrite to lepidocrocite. The influence of these structural transformations on contaminant removal was profound with the ferrihydrite that formed on mZVI inducing rapid adsorption of formate and moderating reactions of mZVI with oxygen and/or water. Although surface passivation of mZVI was significant, the effectiveness of the ensuing heterogeneous redox reactions in the mZVI/O2 system, as characterized by the molar ratio of oxidized formate to consumed Fe(0) (i.e., 13.7 ± 0.8 μM/M), was comparable to that for nZVI (16.5 ± 1.4 μM/M). The results of this study highlight the potential of mZVI for the oxidative degradation of target organics in preference to nZVI despite its lower intrinsic reactivity though some means (either natural or engineered) of inducing continual depassivation of the iron oxyhydroxide-coated mZVI would be required in order to maintain ongoing oxidant production. Graphical abstract: Highlights: nZVI and mZVI oxidize a simple target contaminant at similar rates. Passivating layers of lepidocrocite form on nZVI while ferrihydrite forms on mCDI. Ferrihydrite at mZVI surface is critical to co-location of contaminant and oxidant. Rapid rate of reaction of nZVI with water lowers its efficiency as an oxidant.